Inattention vs switching costs: An analysis of consumers' inaction in choosing a water tariff - Florian Heiss; Carmine Ornaghi; Mirco Tonin (Heinrich Heine University Düsseldorf, Düsseldorf Institute for Competition Economics (DICE), 2021)
This paper studies consumers' choice between two different water tariffs. We document a large inaction in a novel setting where customers face a binary decision and receive simple, detailed and personalized information about the financial savings they would obtain if they were to switch water tariff. Our empirical framework separates two sources of inertia: inattention and switching costs. The model estimates that half of the 50 thousand customers in our sample are not aware of the opportunity they are offered and that, conditional on paying attention, median switching costs are 89. A model where all customers are assumed to pay attention instead delivers implausibly high switching costs, with a median of 482. Looking at the characteristics of the households, our results confirm previous findings that areas where households have higher levels of education or the proportion of minorities is lower, display a higher responsiveness to potential savings. The new insight offered by our analysis is that it is the level of attention, and not the switching costs, that differ across levels of education and ethnicity. Our findings suggest that policies aimed at increasing attention can play a central role in fostering competition among suppliers and reducing inequalities.
Keywords: D12; L95; Q25; 330; inattention; switching costs; tariffs; water